Regulation of glutamate transporter 1 (GLT-1) gene expression by cocaine self-administration and withdrawal. (January 2018) - Kim, Ronald; Sepulveda-Orengo, Marian T.; Healey, Kati L.; Williams, Emily A.; Reissner, Kathryn J.
Abstract: Downregulation of the astroglial glutamate transporter GLT-1 is observed in the nucleus accumbens (NAc) following administration of multiple drugs of abuse. The decrease in GLT-1 protein expression following cocaine self-administration is dependent on both the amount of cocaine self-administered and the length of withdrawal, with longer access to cocaine and longer withdrawal periods leading to greater decreases in GLT-1 protein. However, the mechanism(s) by which cocaine downregulates GLT-1 protein remains unknown. We used qRT-PCR to examine gene expression of GLT-1 splice isoforms (GLT-1A, GLT-1B) in the NAc, prelimbic cortex (PL) and basolateral amygdala (BLA) of rats, following two widely used models of cocaine self-administration: short-access (ShA) self-administration, and the long-access (LgA) self-administration/incubation model. While downregulation of GLT-1 protein is observed following ShA cocaine self-administration and extinction, this model did not lead to a change in GLT-1A or GLT-1B gene expression in any brain region examined. Forced abstinence following ShA cocaine self-administration also was without effect. In contrast, LgA cocaine self-administration and prolonged abstinence significantly decreased GLT-1A gene expression in the NAc and BLA, and significantly decreased GLT-1B gene expression in the PL. No change was observed in NAc GLT-1A gene expression one day after LgA cocaine self-administration, indicating withdrawal-induced decreases in GLT-1A mRNA. In addition, LgA cocaine self-administration and withdrawal induced hypermethylation of the GLT-1 gene in the NAc. These results indicate that a decrease in NAc GLT-1 mRNA is only observed after extended access to cocaine combined with protracted abstinence, and that epigenetic mechanisms likely contribute to this effect. Highlights: GLT-1 mRNA was examined after different paradigms of cocaine self-administration. ShA self-administration and extinction did not affect GLT-1 mRNA levels. ShA self-administration and abstinence did not affect GLT-1 mRNA levels. LgA self-administration/withdrawal decreased GLT-1A/1B in a region-specific manner. LgA self-administration and withdrawal led to hypermethylation of the GLT-1 gene.